The Anabaptist Movement, the Mennonite Church, the Baptist Church and its Implications for Christian Education - Kristiani Yanti Kana (Indonesian Journal of Christian Education and Theology, 2026)
The Anabaptist movement was one of the significant movements within the sixteenth-century Radical Reformation that greatly influenced the development of Christian theology and education. From this movement emerged the Mennonite tradition and significant influences on the Baptist Church, particularly regarding believer’s baptism, religious freedom, and Christian discipleship. This article aims to analyze the theological and pedagogical ideas of the Anabaptist movement, the Mennonite Church, and the Baptist Church, as well as their implications for Christian Religious Education. The method used in this study is library research with a descriptive analytical approach toward various theological and Christian educational literatures. The findings reveal that these three traditions emphasize the importance of personal conversion, discipleship, Christian character formation, exemplary living, and community-based education.